Use of milling equipment goat filth as fertilizer which mixed with dolamits in the village persadanta Scub-District Barusjahe Districts Karo - Br Sembiring, Helmina; Ginting, Junedi (Talenta Publisher, 2019)
This community service aims to increase insight into the use of goat manure as fertilizer mixed with dolomite with very minimal expenditure of money using equipment provided by the USU Community Service Team in 2019 which was carried out in Persadanta Village, Barusjahe District, Karo District. The specific target of this service is to increase the productivity of agricultural products related to the use of fertilizers and be able to sell them to other communities, so as to increase community income for the achievement of a prosperous community, especially farmer groups in the village. So far, the people directly use goat manure as fertilizer for their plants. This is very detrimental to the community because the process is long to be able to become fertilizer and reduced nutrient elements that are poured into plants openly. Besides the use of dolomite mixed with goat manure is very good because dolomite is very much and easily obtained in Tanah Karo. Therefore, it is necessary to give insight and knowledge to the community, especially the Rumah Rih Hamlet Village Group Persadanta Village about the use of goat manure mixed with dolomite. So that people who have been buying fertilizer at a high price can manage it themselves by using the goat manure grinding equipment with the method to be implemented, namely counseling, training, direct practice and work evaluation.